Immunohistochemical expression of ezrin in oral potentially malignant disorders-A descriptive study - Raghini Mohanraj; Pratibha Ramani; Priya Premkumar; Anuja Natesan; Herald J Sherlin; Gheena Sukumaran (Wolters Kluwer Medknow Publications, 2017)
Introduction: Ezrin, also known as cytovillin, is a member of the ERM family of protein. Ezrin cross-links actin filament with the plasma membrane. They are involved in the formation of microvilli, cell-cell adhesion, maintenance of cell shape, cell motility, and membrane trafficking. Recent analysis reveals their involvement in signaling pathways. Ezrin is highly expressed in several types of human cancers, and correlation between its immunoreactivity and histopathological data as well as the patient outcome has previously been studied. Objective: The objective of the study was to analyze the immunohistochemical expression pattern of ezrin in oral potentially malignant disorders (OPMDs), namely, oral submucous fibrosis (OSMF) with different grades and clinically leucoplakia (hyperkeratosis with various degree of dysplasia) and its use as a predictive marker for malignant transformation. Subjects and Methods: Sample size n = 43, histopathologically confirmed cases of OPMDs (13 cases of OSMF with different grades and 30 cases of clinically leukoplakia) were retrieved from the Department of Oral and Maxillofacial Pathology. Immunohistochemistry was done using anti-ezrin antibody, and the expression was graded in terms of proportion and intensity. Results: There was a significant expression of ezrin in OPMDs, and its cytoplasmic shift can be used as a predictive marker for malignant transformation. Conclusion: The findings of the current study revealed that the expression of ezrin in OPMDs may be related to the progression of the disease.